Implementasi Information Reminder System Menggunakan Data Sharing Pada Keluarga Berbasis Web - Yefta, Johanes; Dasawati, Elis Sondang (Jurnal Informatika dan Bisnis, 2024)
The adaptation of technology in an instantaneous era with all its sophistication makes individuals rely more on technology to help them in doing their daily work. Almost all aspects have been facilitated through the help of the system. However, it cannot be denied that there are still many families who record their monthly expenditure information needs manually, resulting in limited collaboration and effectiveness between members. Limited collaboration in the family can be overcome with a digital reminder system that can be implemented to help family members to remember information related to monthly expenses so that families can see, monitor and control their financial flow. The system can be implemented using React as the main framework and Firebase as a database service that is directly integrated with the data sharing model using the internet as a platform to manage and access data in a single-entry manner. In practice, the researcher applied field research (qualitative method) as the main method to obtain data. The researcher also chose the Personal Extreme Programming (PXP) approach as a method as well as a technique for measuring data in this research. The final solution of this research is producing a web-based family recording and reminder application. This application has features to record monthly spending information, schedule monthly and annual bills and record daily spending needs. Through a directly synchronized cloud service, users can access their accounts from any internet-connected device. The conclusion obtained from this research is that the development of this application can assist families in recording and reminding information directly related to monthly expenses in one website container that can be accessed on various devices with only an internet connection.